Future Residential Water Heating Prospects in Brazil: A Scenario Building Ground Analysis - Sgarbi, Felipe de Albuquerque; Guilherme, Danielle Johann; Croso, Taluia; Fossa, Alberto; dos Santos, Edmilson Moutinho; Fagá, Murilo Tadeu Werneck (Future Studies Research Journal: Trends and Strategies, 2014)
In Brazil, electricity is the prime energy carrier for bath shower heating purposes. However, since analyses indicate that expansion of the country´s electricity generation capacity shall spruce from an increased non-renewable sources’ stake in detriment to that of hydroelectricity, high electricity consumption rates that spring from home end uses of the kind have drawn the attention of those who are involved with local energy planning. Furthermore, massive use of electric showers in a short timeframe largely drive electricity demands to culminate in peak loads. For water heating purposes, this context has favoured an alternative to electricity, deemed feasible from both an efficiency and energy infrastructure standpoint: promote fuel gas consumption (liquefied petroleum gas and natural gas in particular). A scenario methodology is herein employed to map electric shower use related variables and players and assess the future behaviour of the core elements that condition resorting to this technology. Thereafter, strategies and opportunities to promote the rational consumption of the country´s power sources ground on the increased use of fuel gases for residential water heating purposes are discussed.